Sistem Pendukung Keputusan Menentukan Aparatur Sipil Negara Terbaik Pada Dinas Pengelolaan Sumber Daya Air Unit Pelaksana Teknis Dinas dengan Metode Simple Additive Weighting - Sumarno Sumarno; Indra Gunawan; Heru Satria Tambunan (STMIK Budi Darma, 2019)
The Water Resources Management Agency has the main duty to organize some district government affairs in the field of water resources management based on the principle of autonomy which becomes the authority, deconcentration and assistance duty and other tasks in accordance with the policy stipulated by the Regent based on the applicable laws and regulations. The performance appraisal undertaken in this agency is intended for the Civil State Apparatus. the assessment process is carried out for measuring and improving the performance of the State Civil Apparatus so as to encourage these employees to work better. From the assessment of the superior can be determined the best employee or promotion position. The performance appraisal process conducted by the culture and tourism office is still done manually, so the performance calculation tends to be subjective and takes a long time. Therefore, in order that the process of appraising employee performance becomes more objective and practical, it should be done computerized by developing an application that implements the right methods. This subjectivity can be overcome with decision support system using Simple Additive Weighting (SAW) method based on existing assessment criteria. The end result of research is the rank of employee value that can be a consideration for decision makers in the determination of promotions as well as an encouragement for employees to work better and productive.